An Analysis of Protein Consumption in India Through Plant and Animal Sources. Issue 4 (December 2018) - Rampal, Priya
Background: India became self-sufficient in food because of the Green Revolution in the 1960s. However, both the technological innovation and policy support have been biased toward cereals. It is expected that cereals are the major source of proteins in the diet. In recent years, the consumption of cereals is declining in spite of increasing output due to declining preference. Therefore, the country needs to increase production and consumption of pulses to meet the nutritional requirements of the population. Objectives: This article discusses the trends in pulse and protein consumption over the years. Further, it focuses on the substitutability and complementarity between various sources of proteins. Methods: A seemingly unrelated regression estimation (SURE) framework is used to study the price and income effect on proteins from different sources—cereals and pulses (plant sources), milk and milk products, animal sources such as eggs, fish, and meat, and other sources of protein. Results: It is found that the expenditure on proteins is large and significant. As income increases, consumption of proteins increases. Higher disposable incomes have led to higher demand of animal sources of proteins. There are significant food price effects in our analysis—negative for cereals and positive for eggs. As the price of pulses increases, consumption of animal sources of proteins increases. Conclusion: It becomes important to contain volatility in pulse prices given that it is a major source of plant protein. States distributing pulses in the Public Distribution System show higher consumption of proteins than other states.